Review on Effects of Sowing Methods and Types of Inorganic Fertilizers on Growth Yield and Yield Component of TEFF [Eragrostis TEF (ZUCC.) - Damte Balcha Gadana (CV. Literasi Indonesia, 2021)
Most farmers’ practices broadcast sowing methods and productivity is less. Soil fertility maintenance is a major concern in tropical Africa which needs to tackle soil fertility depletion as a fundamental constraint. Similarly, the traditional way of planting tef reduces the amount of grain production, promotes competition for inputs, and causes severe lodging. This paper aimed to review the interaction effects between seed sowing methods and different types of inorganic fertilizers on the growth and yield of teff. In Ethiopia, recent research indicates planting method (row planting and broadcasting) affects the yield and yield components of teff. The review indicates the yield components include heading and maturity, plant height, first growth rate, number of tiller and panicle, thousand seed weight, grain, straw, and total biomass yields and harvest index high in Method of Row sowing compared to broadcast in Ethiopia but Days to emergence and panicle length were more affected by broadcasting. In economical acceptance, Row sowing was found to be economically acceptable with more income from grain yield than broadcasting.